ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE JOB ORDER COSTING SEBAGAI DASAR PENENTUAN HARGA JUAL (STUDI KASUS MEUBEL NAFIR DESIGN KUTA BADUNG BALI) - Mia Saphira; Balqis Nurul Aisa; Roni Yanto (Accounting Journal of Ibrahimy (AJI), 2023)
This study aims (1) to describe the mechanism for calculating the cost of production at Furniture Nafir Design Kuta Badung (2) to describe the analysis of calculating the cost of production using the Job Order Costing method at Furniture Nafir Design Kuta Badung. The method that researchers used in data collection. the result of this field research which were not contaminated from the opinions or ideas of researchers include discussions on approaches and types of research, presence of researchers, research locations, data sources, data collection techniques, data analysis techniques, techniques for checking the validity of data, and research stages conducted by researchers in conducting research. The conclusions in this study (1) in calculating the cost of production of Furniture Nafir Design still uses simple (traditional) calculations, namely only calculating raw material costs, labor costs, and factory overhead costs which only charge electricity and telephone costs. Furniture Nafir Design also did not calculate in detail the costs that should have been charged to factory overhead costs, resulting in inaccurate calculations and discrepancies with calculations using the Job Order Costing method. The difference for photo frame products is Rp. 110,307 and for mirror frame products is Rp. 156,112. (2) The calculation of the cost of production using the Job Order Costing method is more appropriate to be applied to Furniture Nafir Design Kuta Badung because the calculation of the cost of production using the Job Order Costing method is more accurate and detailed. By using the Job Order Costing method, costs that should be charged can be calculated into the calculation of the cost of production, so that it can be easier to make decisions in determining prices for products ordered by consumers